The Relationship Between Arm Muscle Strength And Abilities Passing Down Volleyball Games In Class V Students Of Sdn Inpres Bertingkat Waena T.A 2023/2024 - Tampi, Siane Maria; Kobak, Nonamina; Mangolo, Ewendi W (Jurnal Pendidikan Jasmani (JPJ), 2025)
The aim of this research is to find out how big the relationship is between arm muscle strength and down passing ability in class V students at SDN Inpres, Waena, T.A 2023/2024. The population of this research is the fifth grade students of SDN Inpres Berangkat Waena totaling 30 students. The research sample is the fifth grade students of SDN Inpres Bertier Waena who took the total of 28 students. Arm Muscles with Lower Passing Ability. The analysis technique used is Product Moment Correlation. The research results show that there is a significant relationship between arm muscle strength. With Lower Passing Ability in Class V Students of SDN Inpres Berangkat Waena.